A theoretical study of H2O2 as the surrogate of dose in minibeam radiotherapy, with a diffusion model considering radical removal process: reseach article - Zhang, Tengda; Garcia-Calderón, Daniel; Molina-Hernández, Miguel; Leitão, Joana; Hesser, Jürgen; Seco, Joao (Medical physics, 2023)
Background Minibeam radiation therapy (MBRT) is an innovative dose delivery method with the potential to spare normal tissue while achieving similar tumor control as conventional radiotherapy. However, it is difficult to use a single dose parameter, such as mean dose, to compare different patterns of MBRT due to the spatially fractionated radiation. Also, the mechanism leading to the biological effects is still unknown. Purpose This study aims to demonstrate that the hydrogen peroxide (H2O2) distribution could serve as a surrogate of dose distribution when comparing different patterns of MBRT. Methods A free diffusion model (FDM) for H2O2 developed with Fick's second law was compared with a previously published model based on Monte Carlo & convolution method. Since cells form separate compartments that can eliminate H2O2 radicals diffusing inside the cell, a term describing the elimination was introduced into the equation. The FDM and the diffusion model considering removal (DMCR) were compared by simulating various dose rate irradiation schemes and uniform irradiation. Finally, the DMCR was compared with previous microbeam and minibeam animal experiments. Results Compared with a previous Monte Carlo & Convolution method, this analytical method provides more accurate results. Furthermore, the new model shows H2O2 concentration distribution instead of the time to achieve a certain H2O2 uniformity. The comparison between FDM and DMCR showed that H2O2 distribution from FDM varied with dose rate irradiation, while DMCR had consistent results. For uniform irradiation, FDM resulted in a Gaussian distribution, while the H2O2 distribution from DMCR was close to the dose distribution. The animal studies’ evaluation showed a correlation between the H2O2 concentration in the valley region and treatment outcomes. Conclusion DMCR is a more realistic model for H2O2 simulation than the FDM. In addition, the H2O2 distribution can be a good surrogate of dose distribution when the minibeam effect could be observed.